THE EFFECT OF MODIFIED PURSED LIPS BREATHING TROUGH PLAT ON RESPIRATORY RATE AND OXYGEN SATURATION IN CHILDREN WHIT PNEUMONIA - Sastriani, Sastriani; Yuliani, Eva; Mursyid, Aco; Damayanti, Risna; Nurwahita, Nurwahita (Jurnal Keperawatan, 2025)
Pneumonia is the most common inflammatory lung disease in children. One of the symptoms of pneumonia is an increased respiratory rate and decreased oxygen saturation due to alveolar inflammation, which makes it difficult for the body to obtain oxygen. A non-pharmacological therapy that can be applied is tongue-blowing play based on the principles of Pursed Lips Breathing (Pursed Lips Blowing Play). This study aims to determine the effect of pursed lips blowing play on reducing respiratory rate and increasing oxygen saturation in children with pneumonia. The research design used was a Quasi-Experimental study with a pre- and post-test without a control group. The study was conducted at Pamboang Community Health Center with a sample size of 15 respondents, selected using purposive sampling. Univariate and bivariate analyses were performed using the Paired t-test and Wilcoxon test. The results showed a significant effect on changes in respiratory rate and increased oxygen saturation after tongue-blowing play, with p-values of 0.001 and 0.001, respectively. Based on these findings, pursed lips blowing play is recommended as a nursing intervention for pneumonia patients.